JARIMU Application as a Self-Development Medium for Children with Intellectual Disabilities - Apriliani, Lia; Rochyadi, Endang (Department of Special Education, 2023)
Introducing money is a self-development skill for children with intellectual disabilities that is very important in their lives. However, this is often a problem and is misunderstood by children with intellectual disabilities. This confusion occurs because they are often presented directly as money, while their value and function are not well understood. As a result, the direct use of money as a medium becomes less attractive, has no meaning, and is only used as a toy that has no direction. The purpose of this research is to develop an Android-based learning medium that can help people with intellectual disabilities understand money as a whole. This study uses a mixed method with a sequential exploratory model design. This application test uses the Black Box, and the results show that the JARIMU application can be used operationally properly. Based on the feasibility test, the JARIMU application has a very good acceptance rate with a percentage of 86.029%. The implications of these findings are suggested to be applied by schools or teachers in introducing money for children with intellectual disabilities.